Advancements in adsorption efficiency: cationic modified Nanocellulose with Glycidyltrimethylammonium Chloride (GTMAC) for Malathion removal in water - Abdul Razak, Mas Amira Idayu; Mohd Kasim, Noor Azilah; Knight, Victor Feizal; Ahmad Shah, Noor Aisyah; Faiz Norrrahim, Mohd Nor; Jamal, Siti Hasnawati; Kasim, Norherdawati; Md Yasin, Faizah; Wan Yunus, Wan Md Zin (Sami Publishing Company, 2024)
The use of pesticides like malathion has been increased due to agricultural development and the diversification of plant pests and have caused serious impacts towards human health and ecosystem. The aim of this study was to use a material sourced from a bio-waste via cellulose extraction for the preparation of cationic nanocellulose fiber (NC) intended for the uptake of negatively charged ions of malathion pesticides. In this study, we reported the preparation and characterization of cationic functionalized-NC with glycidyltrimethylammonium chloride (GTMAC). The NC and functionalized-NC structural and chemical properties were characterized using Fourier transform infrared spectroscopy (FTIR), Elemental analyzer (CHNS), Field Emission Scanning Electron Microscopy with Energy Dispersive X-Ray Spectroscopy (FESEM-EDX), Transmission electron microscopy (TEM) and Zeta potential. The adsorbent weight (1.0-5.0 mg), contact time (30-150 s), and concentration of malathion (6.0-14.0 mg/L) were studied to determine the optimum condition using the composite central design (CCD) based on the response surface methodology (RSM). The adsorption capacity was obtained 54.34 mg/g with an adsorbent weight of 1.0 mg, contact time of 130 s, and initial concentration of malathion 10.0 mg/L. The results revealed that quadratic model was proper for the prediction adsorption capacity of the adsorbent. The adsorption kinetics and isotherms were examined under optimal conditions. The Langmuir with a coefficients of determination (R2) = 0.9737 and pseudo-first-order with (R2) = 0.9774 were identified as the optimal models. The results showed that the NC-GTMAC can be effective and affordable adsorbent towards malathion in aqueous solution.